Dominance and divergence: Ethnic groups and preferences for redistribution in Southeast Asia - Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2021)
Does identification with dominant ethnic groups lead individuals to diverge in their preferences for redistribution? This paper contributes to the comparative analysis of the role of ethnic background in shaping attitudes towards government's role in reducing income inequalities in Indonesia, Malaysia, Philippines, Singapore and Thailand, where nearly half-a-billion people live and belong to more than sixty ethnic groups. Using a pool of nationally-representative survey data from the five Southeast Asian countries, we first classified the respondents by population dominance of the ethnic groups they claim to belong, and then examine for differences across members of dominant ethnic groups in their preferences for government redistribution. Relative to the biggest ethnic group, the second biggest ethnic group is found to have less preference for redistribution, after controlling for other factors. No systematic differences in their redistributive preferences are found, however, between the biggest ethnic group and other smaller groups. The results are fairly robust even after accounting for the possible moderating effects of income status, trust in government and in people, subjective social mobility, concerns about social fairness, and views on the importance of fate in one's life. Moreover, the results hold out even in the sub-sample of low-income people for whom economic considerations more than ethnicity are expected to determine their redistributive preferences. Notwithstanding the importance of shared norms or beliefs in aligning he social choices of people with same ethnic or racial background, our results suggest their population sizes, which possibly reflect their relative influence over domestic policies, also matter.
Keywords: H20; H53; I39; Z10; 330; Redistribution; ethnic dominance; income inequality; social mobility; trust; Southeast Asia